2019
DOI: 10.1039/c9nr01863h
|View full text |Cite
|
Sign up to set email alerts
|

Self-assemblies of nucleolipid supramolecular synthons show unique self-sorting and cooperative assembling process

Abstract: Cocktails of nucleolipids and nucleosides serve as powerful supramolecular synthons to build unique architectures and gels with remarkably enhanced mechanical strength via a self-sorting and cooperative self-assembling process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Mixtures of adenosine and 84c-d were studied, and their self-sorting or co-assembling properties were analyzed. Increases in mechanical strength were observed in several gel mixtures when compared to gels formed from the individual components [98]. This study showed that mixtures of gelators can be used to tune mechanical strength and construct unique higher ordered microarchitectures.…”
Section: From Ribose Derivativesmentioning
confidence: 70%
See 2 more Smart Citations
“…Mixtures of adenosine and 84c-d were studied, and their self-sorting or co-assembling properties were analyzed. Increases in mechanical strength were observed in several gel mixtures when compared to gels formed from the individual components [98]. This study showed that mixtures of gelators can be used to tune mechanical strength and construct unique higher ordered microarchitectures.…”
Section: From Ribose Derivativesmentioning
confidence: 70%
“…This pH sensitive biocompatible metallogel drug delivery system shows potential as a soft material for biomedical applications. Nuthanakanti et al designed and synthesized adenosine-and uridine-fatty acid conjugates as shown in Figure 50 [98]. The adenosine-diesters 83a-d did not form gels in organic solvents.…”
Section: From Ribose Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, proteins, like microtubules and actin filaments, are self-sorted on the molecular level in living cells [3]. Furthermore, the smaller molecules of life such as sugars [4], peptides, and fatty acids [5] undergo self-sorting in the construction of a cell [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…e CNS method can analyze the whole process of the football match and the collaborative network established by it is both flexible and dynamic, which can not only reflect the overall situation of the team but also track the dynamics of each player during the game. is is the case in the study by Buldu et al [5,14]. is paper mainly uses the CNS method to analyze the cooperation problems in football teams and through the use of a large number of match data to build a matching network and then to reveal the mechanism of team cooperation, focusing on the team's attack and defense strategy.…”
Section: Introductionmentioning
confidence: 99%